2021
DOI: 10.1016/j.adro.2020.10.028
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose-Rate Brachytherapy for the Treatment of Basal and Squamous Cell Carcinomas on Sensitive Areas of the Face: A Report of Clinical Outcomes and Acute and Subacute Toxicities

Abstract: Basal cell and cutaneous squamous cell carcinoma are common malignancies (keratinocyte carcinomas [KCs]). Surgical resection is the standard of care. Radiation using high-dose rate brachytherapy (HDR-BT) may serve as a superior alternative where surgical scars may be of cosmetic concern or in elderly patients with significant comorbidity. We aim to describe the clinical and cosmetic outcomes as well as posttreatment radiation toxicities associated with HDR-BT in patients who were treated for KCs of the face. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…Also, cosmetic results of the patients included are very promising, with more than 96% of the cases showing good/ excellent results detected at follow-up. Taylor et al [26] observed grade 2 toxicity at completion of treatment in 85% of patients and no grade 3 or higher skin toxicity. Moreover, Gauden et al in a cohort of 200 patients reported G1 acute skin toxicity in 168 treated lesions (71%), G2 in 81 (34%), and good or excellent cosmesis in 208 cases (88%).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Also, cosmetic results of the patients included are very promising, with more than 96% of the cases showing good/ excellent results detected at follow-up. Taylor et al [26] observed grade 2 toxicity at completion of treatment in 85% of patients and no grade 3 or higher skin toxicity. Moreover, Gauden et al in a cohort of 200 patients reported G1 acute skin toxicity in 168 treated lesions (71%), G2 in 81 (34%), and good or excellent cosmesis in 208 cases (88%).…”
Section: Discussionmentioning
confidence: 98%
“…Taylor et al . [ 26 ] observed grade 2 toxicity at completion of treatment in 85% of patients and no grade 3 or higher skin toxicity. Moreover, Gauden et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations